2009
DOI: 10.1016/j.bbrc.2009.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Related lectins from snowdrop and maize differ in their carbohydrate-binding specificity

Abstract: Searches in an EST database from maize revealed the expression of a protein related to the Galanthus nivalis (GNA) agglutinin, referred to as GNAmaize. Heterologous expression of GNAmaize in Pichia pastoris allowed characterisation of the first nucleocytoplasmic GNA homolog from plants. GNAmaize is a tetrameric protein which shares 64% sequence similarity with GNA. Glycan microarray analyses revealed important differences in the specificity. Unlike GNA, which binds strongly to high-mannose N-glycans, the lecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 16 publications
1
45
0
Order By: Relevance
“…The legume lectin family is another large group of plant lectins that includes the various high mannose-binding lectins (3). Importantly, some of these high mannose-binding plant lectins exhibit a strong anti-HIV activity, but others are weak or completely inactive (4,5). Such different biological activities virtually depend on the diverse carbohydrate specificities of these plant lectins.…”
mentioning
confidence: 99%
“…The legume lectin family is another large group of plant lectins that includes the various high mannose-binding lectins (3). Importantly, some of these high mannose-binding plant lectins exhibit a strong anti-HIV activity, but others are weak or completely inactive (4,5). Such different biological activities virtually depend on the diverse carbohydrate specificities of these plant lectins.…”
mentioning
confidence: 99%
“…Recent report on the carbohydrate binding specificities of Galanthus nivalis agglutinin (GNA) and GNA like the lectin from Zea mays (GNA maize ) was determined by glycan array analysis which demonstrated that GNA recognizes mannose weakly, but strongly binds to high mannose type glycans. GNA maize , unlike GNA binds exclusively to high mannose type and complex N-glycans [33]. Considering the exclusive carbohydrate specificity of these lectins towards high mannose type N-glycans commonly occurring in animal glycoproteins, it is speculated that these plant proteins are evolved for defense purpose [13].…”
Section: Resultsmentioning
confidence: 99%
“…All TSHs showed different profiles. pitTSH showed a higher ConA signal, most probably due to a high content in biantennary structures [5,[28][29][30] , and elevated core fucosylation (LCA), but very low level of galactose (ECL), α2,3-(WGA) and α2,6-sialic acid (SNA) because its glycans terminate in sulfated-GalNAc [5,10] ( fig. 2 a).…”
Section: Discussionmentioning
confidence: 99%
“…Again, most group B assays showed quite a superior binding capacity, with the highest signals being observed with B2 and B3 for both calibrations. [28] , Galanthus nivalis lectin (GNL) binds hybrid and high-mannose glycans [29] , Lens culinaris agglutinin (LCA) recognizes preferentially core-α1,6-fucosylated glycans [30] , Erythrina cristagalli lectin (ECL) binds terminal β1,4-galactose of complex glycans [30] , wheat germ agglutinin (WGA) binds α2,3-sialic acids [30] , and SNA binds α2,6-sialic acids [30] . Error bars indicate standard deviation.…”
Section: Quantitative Antibody Bindingmentioning
confidence: 99%